Haití: de la ‘invisibilidad’ de un territorio a la concreción de proyectos que fortalezcan su autonomía - Lorda, María Amalia (2012)
Haiti, known in colonial times as "the Pearl of the Antilles", its economy was organized around the production of sugar supplied through France the rest of Europe. Thus 70% of the sugar was consumed in Europe, and over 60% of the coffee. With a logic pursuing maximize yields, sought slave labor in sub-Saharan Africa population that directly replaced the original. So begins to approach development of a type of economy in Haiti, which would have serious environmental consequences to the present. Today is the poorest country of America, with a life expectancy of about 60, and the illiteracy rate of 52%. Located in a tropical area, they often suffer the impact of tropical storms and cyclones, as a result of excessive logging of native forestry, floods compound the problems, in addition to health problems inherent in a level life with so many deficiencies, and the preponderance of small farms in rural areas, leading to establish a scenario of extreme vulnerability. In 2010, sad news would put Haiti on the global center stage: the earthquake in March of that year that affected the area of Puerto Príncipe leaving about 300,000 deaths and more than a million homeless. At present, the presence of whole neighborhoods living in tents in public spaces, are expressions of the life of the event. However, since the middle of the last decade have projects that attempt to localize site experience recognized impact on Argentina's attempts to meet the needs of most vulnerable population living in rural areas. This is the Pro Huerta, who for over twenty years in Argentina is developed and proposed in the area of this country from the perspective of international cooperation. Thus, in different departments of Haiti to work together from different countries are launching a social project for food security. The purpose is to analyze the experience territorialization Pro Huerta Haïti from international cooperative approach which Argentina participates with Canada and Haïti. The results and contributions of this research, it was found that in Haiti strengthen social networks, family, solidarity work, health and together contribute to food sovereignty in a country in great need and great vulnerability. It is also interesting to note that the model of South-South Cooperation for Argentina develops from a horizontal view where our country walks with Haiti and Canada in the everyday learning of growing together, where each country has a lot to keep learning.